Synergistic Activity of Rhamnolipid Biosurfactant and Nanoparticles Synthesized Using Fungal Origin Chitosan Against Phytopathogens - Karamchandani, Bhoomika M.; Maurya, Priya A.; Dalvi, Sunil G.; Waghmode, Samadhan; Sharma, Deepansh; Rahman, Pattanathu K. S. M.; Ghormade, Vandana; Satpute, Surekha K. (Frontiers in Bioengineering and Biotechnology, 2022)
Phytopathogens pose severe implications in the quantity and quality of food production by instigating several diseases. Biocontrol strategies comprising the application of biomaterials have offered endless opportunities for sustainable agriculture. We explored multifarious potentials of rhamnolipid-BS (RH-BS: commercial), fungal chitosan (FCH), and FCH-derived nanoparticles (FCHNPs). The high-quality FCH was extracted from Cunninghamella echinulata NCIM 691 followed by the synthesis of FCHNPs. Both, FCH and FCHNPs were characterized by UV-visible spectroscopy, DLS, zeta potential, FTIR, SEM, and Nanoparticle Tracking Analysis (NTA). The commercial chitosan (CH) and synthesized chitosan nanoparticles (CHNPs) were used along with test compounds (FCH and FCHNPs). SEM analysis revealed the spherical shape of the nanomaterials (CHNPs and FCHNPs). NTA provided high-resolution visual validation of particle size distribution for CHNPs (256.33 ± 18.80 nm) and FCHNPs (144.33 ± 10.20 nm). The antibacterial and antifungal assays conducted for RH-BS, FCH, and FCHNPs were supportive to propose their efficacies against phytopathogens. The lower MIC of RH-BS (256 μg/ml) was observed than that of FCH and FCHNPs (>1,024 μg/ml) against Xanthomonas campestris NCIM 5028, whereas a combination study of RH-BS with FCHNPs showed a reduction in MIC up to 128 and 4 μg/ml, respectively, indicating their synergistic activity. The other combination of RH-BS with FCH resulted in an additive effect reducing MIC up to 128 and 256 μg/ml, respectively. Microdilution plate assay conducted for three test compounds demonstrated inhibition of fungi, FI: Fusarium moniliforme ITCC 191, FII: Fusarium moniliforme ITCC 4432, and FIII: Fusarium graminearum ITCC 5334 (at 0.015% and 0.020% concentration). Furthermore, potency of test compounds performed through the in vitro model (poisoned food technique) displayed dose-dependent (0.005%, 0.010%, 0.015%, and 0.020% w/v) antifungal activity. Moreover, RH-BS and FCHNPs inhibited spore germination (61–90%) of the same fungi. Our efforts toward utilizing the combination of RH-BS with FCHNPs are significant to develop eco-friendly, low cytotoxic formulations in future.